ANALISIS PEMENUHAN HAK-HAK REPRODUKSI PADA IBU-IBU PKK RT 01 RW 03 KELURAHAN BINA WIDYA KEC. TAMPAN - octa dwienda ristica; Widya Juliatri (Institut Kesehatan dan Teknologi Al Insyirah, 2019)
The issue of women's rights is a study that received a lot of attention. The fact shows that the fate of women in western countries that are more advanced is not much different from other countries. This condition was also found in Indonesia. Various cases of reproductive rights violations can be seen from many rape cases, including marriage, coercion, prohibition of abortion, sexual harassment, torture, coercion on the use of contraception, lack of easy access to information about reproductive health problems, high rates of sexually transmitted infections ( STIs, including HIV / AIDS in women, and various forms of discrimination that make women less dominant. The purpose of this study was to determine the extent to which reproductive rights were fulfilled in PKK women RT 01 RW 03, Bina Widya Sub-district, Tampan District. This type of research is a qualitative study with in-depth interviews and limited observation. The informants in this study were women who were married and joined in the PKK and as key informants were PKK administrators and as supporters were PKK husbands and mothers. The analysis used in this study is qualitative analysis (content analysis). The results in this study are expressing that the fulfillment of reproductive rights in PKK women RT 01 and RW 03 Bina Widya sub-district Tampan District is almost fulfilled even though there are some assumptions that specialize in matters of pregnancy, giving birth to using family planning is women's business. The need for special health education discusses reproductive rights alone and in a comprehensive manner to strengthen the knowledge of the reproductive rights of PKK mothers by involving husbands and families.